2015
DOI: 10.2105/ajph.2015.302753
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Rates and State Laws Regulating Access and Exposure to Handguns

Abstract: Our results were supportive of a potentially vital role in suicide prevention for state legislation that limits access and exposure to handguns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 17 publications
7
66
0
1
Order By: Relevance
“…Although we certainly agree that mental illness is an important factor in suicide and that individual factors ranging from poverty to religious affiliation might have an important role in the development of suicidal desire in many individuals, our results indicate that such factors alone do not explain the association between guns and suicide. Our findings are thus highly consistent with the robust literature base supporting the utility of means safety in suicide prevention (Anestis & Anestis, ; Anestis et al., ; Kreitman, ; Oliver & Hetzel, ; Pirkis et al., ). Furthermore, our results provide a rebuttal to the notion of means substitution (Daigle, ), as gun ownership predicted overall state suicide rates, not simply firearm suicide rates.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although we certainly agree that mental illness is an important factor in suicide and that individual factors ranging from poverty to religious affiliation might have an important role in the development of suicidal desire in many individuals, our results indicate that such factors alone do not explain the association between guns and suicide. Our findings are thus highly consistent with the robust literature base supporting the utility of means safety in suicide prevention (Anestis & Anestis, ; Anestis et al., ; Kreitman, ; Oliver & Hetzel, ; Pirkis et al., ). Furthermore, our results provide a rebuttal to the notion of means substitution (Daigle, ), as gun ownership predicted overall state suicide rates, not simply firearm suicide rates.…”
Section: Discussionsupporting
confidence: 90%
“…We utilized the same statewide demographic variables reported in Anestis and Anestis (). These included the percentage of the state that was male, the percentage of the state that was White, the percentage of the state aged 25 years or higher that had obtained a college degree, the percentage of the state living beneath the poverty line, and the state population density.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, any policies that generally reduce access to firearms by individuals who may be at risk for suicide are critical to prevent suicide. Such policies may include, but are not limited to, universal background checks including permit-to-purchase laws, 24 mandatory waiting periods 25 and policies to support or incentivise interventions at other levels of the model (such as a policy that provides funding to train healthcare providers on lethal means safety counselling). Enacting evidence-based firearms violence prevention policies is a societal-level intervention that will enable and support actions at subsequent levels of the SEM while contributing to a shift in cultural norms towards (1) acknowledgement of the role of firearms in suicide; (2) acceptance of reducing firearms access as a viable suicide prevention strategy; and (3) a decrease in the ubiquitous nature of firearms in American society.…”
Section: Societal Levelmentioning
confidence: 99%
“…While the long-term impact of these campaigns cannot be measured yet, and their effectiveness hamstrung by their scale and jurisdictional boundaries, early reports appear positive. One preliminary study found that states that had introduced trigger locks experienced a lower firearm suicide and general suicide rate, although a direct causation remains to be proven (Anestis & Anestis, 2015). There is evidently a delicate balancing act between gun restriction and public safety initiatives, but these examples show that compromise and cooperation is possible.…”
Section: Suicide Mental Health and Reformmentioning
confidence: 99%